Meningkatkan Motivasi Kaum Pelajar Untuk Melanjutkan Ke Jenjang Pendidikan Tinggi - Elly Karmeli; Ika Fitriyani; Sri Rahayu; Kurniawansyah; Ismawati (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Motivation is one of the factors that influence a person's success. Motivation can serve as a driving force for achieving good results. This activity aims to increase the motivation of students or students to continue their education at the university level. Awareness and self-confidence are the keys to self-motivation. The dominant problem that often arises among students is feeling that they are not ready to continue on to college. The high cost of tuition, the lack of access to universities in providing information on scholarships so that parents are desperate to send their children to the university level. In addition, the emergence of unemployment among the community makes parents feel anxious about sending their children to school. The purpose of this activity is to increase the motivation of students to continue their studies at the university level. Through the lecture method, discussions and interviews with the Principal, Teachers, and Students at the School this activity has received a good response so that it broadens and facilitates their information about education. This activity has been running smoothly and there is a spirit of enthusiasm from the students to want to continue their studies in college. In the future, this activity will continue to be improved by holding outreach for parents to open their horizons and make parents aware of the importance of education.